Growth following adversity in sport : a mechanism to positive change - Wadey, Ross; Day, Melissa; Howells, Karen (New York, NY : Routledge, 2021)
Growth Following Adversity in Sport: A Mechanism to Positive Change is the first text to carefully consider the positive changes that may follow adverse experiences in sport at micro (e.g., individual), meso (e.g., dyadic, team), and macro levels (e.g., organizational, cultural). While remaining respectful of the despair and distress that can follow adversity, this comprehensive text aims to provide a narrative of hope to those who have experienced adversity in sport by showcasing the latestadvances in research on growth following adversity. This book covers topics as diverse as: conceptual, theoretical, and methodological considerations; cultural, organizational, and relational perspectives; population-specific insights (e.g., gender, disability, youth); and applied implications (e.g., evidence-based, practice-based). Written and edited by a team of international experts and emerging talents from around the world, each chapter considers the nature and meaning of growth, contains a comprehensive review of empirical research or reflections from professional practice, and offers exciting, novel, and rigorous suggestions for future programs of research that aim to promote positive change in sport to support the safety, wellbeing, and welfare of the people who take part (e.g., athletes, coaches, paid employees, volunteers). Cutting-edge, timely, and comprehensive, Growth Following Adversity in Sport: A Mechanism to Positive Change is essential reading for postgraduate students and scholars in the fields of sport psychology, injury and rehabilitation, sport theory and other related sport science disciplines.
OCLC-licensed vendor bibliographic record.
Keywords: Sports -- Psychological aspects; Sports injuries -- Psychological aspects; Sports injuries -- Rehabilitation; Sports medicine; SPORTS & RECREATION / Sports Psychology; MEDICAL / Sports Medicine; MEDICAL / Physical Medicine & Rehabilitation